Immunopathogenesis of Immune Checkpoint Inhibitor-Related Adverse Events: Roles of the Intestinal Microbiome and Th17 Cells - Anderson, Ronald; Theron, Annette J.; Rapoport, Bernardo L. (Frontiers in Immunology, 2019)
The advent of novel, innovative and effective anti-cancer immunotherapies has engendered an era of renewed optimism among cancer specialists and their patients. Foremost among these successful immunotherapies are monoclonal antibodies (MAbs) which target immune checkpoint inhibitor (ICI) molecules, most prominently cytotoxic T-lymphocyte-associated protein (CTLA-4) and programmed cell death protein-1 (PD-1) and its major ligand, PD-L1. These immunotherapeutic agents are, however, often associated with the occurrence of immune-mediated toxicities known as immune-related adverse events (IRAEs). The incidence of severe toxicities increases substantially when these agents are used together, particularly with CTLA-4 in combination with PD-1 or PD-L1 antagonists. Accordingly, dissociating the beneficial anti-tumor therapeutic activity of these agents from the emergence of IRAEs represents a significant challenge to attaining the optimum efficacy of ICI-targeted immunotherapy of cancer. This situation is compounded by an increasing awareness, possibly unsurprising, that both the beneficial and harmful effects of ICI-targeted therapies appear to result from an over-reactive immune system. Nevertheless, this challenge may not be insurmountable. This contention is based on acquisition of recent insights into the role of the gut microbiome and its products as determinants of the efficacy of ICI-targeted immunotherapy, as well as an increasing realization of the enigmatic involvement of Th17 cells in both anti-tumor activity and the pathogenesis of some types of IRAEs. Evidence linking the beneficial and harmful activities of ICI-targeted immunotherapy, recent mechanistic insights focusing on the gut microbiome and Th17cells, as well as strategies to attenuate IRAEs in the setting of retention of therapeutic activity, therefore represent the major thrusts of this review.